Análisis de las vulnerabilidades y amenazas en el centro de cómputo del laboratorio de la UACS de la UTMACH. - Ramon Guazha, Jazmin Stefany (My University, 2019)
The Technical University of Machala (UTMACH) manages large amounts of data and information related to its academic functions, and it is imperative to have a security system against logical threats, whose actuators are competences of computer auditing. The relevant written work relates the study carried out in schematizing a response plan in case of cyber attacks based on the latent vulnerabilities / threats in the social sciences library, to describe which processes to follow, what measures to take and induce the mechanisms to defend and safeguard computing assets; the investigation is approached from a cognitive, exploratory and heuristic perspective to analyze from several points of view the best alternative in developing a series of coordinated steps / measures, when properly managing virtual resources in the computer center studied, theoretical criteria are also postulated , opinions and integrate tools or benefits that facilitate the use of ICTs, physical / logical controls focused on a structured plan allow adequate solvency against unforeseen events, in addition to having information / data backups, configurations and constant monitoring Through the audit it facilitates maintaining an order in the distribution of knowledge, in addition to coordinating the use of computers, book provision, consulting and integrating resources for the research development of the subjects, it demands a responsibility that must be solved based on a comprehensive plan of management to ensure the proper use of technology as computer.
La Universidad Técnica de Machala (UTMACH) gestiona grandes cantidades de datos e información referentes a sus funciones académicas, siendo de carácter imperioso contar con un sistema de seguridad contra amenazas lógicas, cuyas accionantes son competencias de la auditoria informática. El trabajo escrito pertinente relata el estudio efectuado en esquematizar un plan de respuesta en caso de ciber ataques en función de las vulnerabilidades/amenazas latentes en la biblioteca de ciencias sociales, para describir cuales procesos seguir, qué medidas tomar e inducir los mecanismos para defender y salvaguardar los activos informáticos; se aborda la indagación desde una perspectiva cognitiva, exploratoria y heurística para analizar desde varios puntos de vista la mejor alternativa en desarrollar una serie de pasos/medidas coordinadas, al gestionar adecuadamente los recursos virtuales en el centro de cómputo estudiado, también se postulan criterios teóricos, opiniones e integrar herramientas o prestaciones que faciliten el uso de las TIC`s, los controles físicos/lógicos enfocados a un plan estructurado permiten una solvencia adecuada frente a imprevistos, además de contar con respaldos de información/datos, configuraciones y un monitoreo constante mediante la auditoria facilita mantener un orden en la distribución de conocimientos, además coordinar el uso de computadores, prestaciones de libros, consultar e integrar recursos para el desarrollo investigativo de las asignaturas, demanda una responsabilidad que debe ser solventada en base a un plan integral de manejo para procurar el buen uso de las tecnológicas informáticas.
Keywords: TECNOLOGÍAS DE COMUNICACIÓN E INFORMACIÓN; GESTIÓN; RIESGOS; PLAN DE MANEJO